Racial and gender hierarchies in the administrative and academic management of UFV - Ferreira, Edimara Maria; Teixeira, Karla Maria Damiano (Argumentum, 2022)
This article aims to investigate gender and racial inequalities in the distribution of administrative and academic posts at the Universidade Federal de Viçosa (UFV), Viçosa Campus. It uses Acker’s concept of inequality regimes as its theoretical basis. Data is drawn from the UFV Ethnic-Racial Census, and the information provided by the institution. The results point to the underrepresentation of black women and men in the administrative and academic hierarchy within the UFV. The public policies implemented must consider other social markers, as public and institutional spaces tend to reinforce and perpetuate the gender and race asymmetries present in society.